2017
DOI: 10.1186/s12906-017-1574-x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized controlled trial of the effect of yoga and peer support on glycaemic outcomes in women with type 2 diabetes mellitus: a feasibility study

Abstract: BackgroundType two diabetes is a complex and demanding chronic disease and its impact in a state (Kerala) which leads India in terms of the number of people with Diabetes is profound. Though the male to female ratio among the people with diabetes is roughly equal, women are uniquely and more severely affected. Management of type two Diabetes requires considerable dexterity on the part of the patient to manage drugs, diet and exercise. Therefore, in a low middle-income country like India it is necessary to look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 20 publications
4
65
0
Order By: Relevance
“…With the exception of this study [40] all studies had a low risk of bias of selective outcome reporting. Overall, eight studies were found to have a low risk of bias [25,30,31,34,36,38,39,41]. A proportion of the trials examined in this review had an unclear risk of bias.…”
Section: Quality Assessmentmentioning
confidence: 83%
See 3 more Smart Citations
“…With the exception of this study [40] all studies had a low risk of bias of selective outcome reporting. Overall, eight studies were found to have a low risk of bias [25,30,31,34,36,38,39,41]. A proportion of the trials examined in this review had an unclear risk of bias.…”
Section: Quality Assessmentmentioning
confidence: 83%
“…to determine eligibility for inclusion (see previous section) in the review. Both reviewers agreed that an additional 91 papers should be excluded as they were not primary research studies (i.e., protocol papers; n = 6), unable to retrieve the full-text record (n = 8), they did not meet the inclusion criteria (e.g., the population included men or women but did not isolate results for women, the intervention was not lifestyle related, or was not designed for women with [29,[34][35][36]39], two originated from Europe (one from Italy [37] and one from Turkey [42]), six originated from Iran [26,27,[30][31][32][33] and the remaining three RCTs originated from Asia (one from India [38], Japan [28], and Thailand [41]). The trial conducted in India was a three armed RCT and the one conducted in Japan was a Crossover RCT.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous research studies in the general population have identified that adoption of a healthy lifestyle such as healthy diet, exercise, and weight loss can prevent GDM, however, there are limited researchers who can focus on usual healthy practices in women with GDM [4]. Most researchers have focused on glycemic control [5] throughout the pregnancy for positive maternal and fetal outcomes, but management has been lacking after childbirth to prevent or delay the development of DM in childbearing women [6]. Hence, the researchers decided to assess the perceived risk and abilities for health practices related to prevention of Type II DM among postnatal mothers with GDM.…”
Section: Introductionmentioning
confidence: 99%